Interferon-based treatment is superior to nucleos(t)ide analog in reducing HBV-related hepatocellular carcinoma for chronic hepatitis B patients at high risk. (3rd October 2018) - Ren, Peipei; Cao, Zhujun; Mo, Ruidong; Liu, Yuhan; Chen, Lichang; Li, Ziqiang; Zhou, Tianhui; Lu, Jie; Liu, Yunye; Guo, Qing; Chen, Rong; Zhou, Huijuan; et al.
ABSTRACT: Background : The effect of nucleos(t)ide analogs (NAs) versus interferon (IFN) on the occurrence of hepatocellular carcinoma (HCC) in chronic hepatitis B (CHB) is controversial. We assessed whether antiviral strategy affected HCC development in CHB patients at different HCC risks. Methods : 1112 CHB patients with antiviral therapy were included in this retrospective study. Patients treated with NAs only were classified into NAs group ( n  = 682) while those received IFN treatment with or without NAs were defined as IFN group ( n  = 430). Propensity score matching (PSM) was applied to minimize baseline differences. Results : Totally, 31 patients developed HCC during follow-up (median 5.41 years). The cumulative HCC incidence at 10 years was significantly lower in the IFN group than NAs group (2.7% vs 8.0%, p  < 0.001). Similar results were obtained in the PSM-cohort. Patients with IFN-based treatment were less likely to develop HCC than those with NAs (Hazard ratio = 0.15; 95% CI 0.04–0.66; p  = 0.012). Subgroup analyses demonstrated that this superiority of IFN in reducing HCC development was obvious in patients at high- but not low-risk of HCC. Conclusions : Reduction of HCC development was more significant in CHB patients at higher HCC risk with IFN-based therapy than NAs treatment.